THE DISCRIMINATION OF MULTICULTURALISM ON MUSLIM WOMEN DRESS CODE (HIJAB) - Hamza Manu; Raja Hisyamuddin; Muhammed Zaidi bin Abdulrahman (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The challenges and discrimination facing the Hijab in the contemporary world against the Muslim women is definitely a worrisome. The objective of this paper is to make a conceptual exertion relating to the challenges and discrimination facing the Hijab in the contemporary multicultural society. The concepts of Hijab, Multiculturalism were discussed. We also looked at the social, economic, psychological, and cultural concepts as designed in the conceptual framework of the study. The paper explained the objectives off the hijab from the Islamic point of view covering obligation, religiosity, chastity, modesty, and piety. The study concludes that ignorance and lack of piety, modesty, and religiosity were among the major challenges responsible for the negligence of practicing the commandment of wearing hijab by some Muslim women. In addition to that, lack of consciousness of Almighty Allah by many Muslim woman, liberalism, western civilization, fashioning the hijab, modern Medias, and several others are some of the major challenges facing the hijab in the Muslim world.